Thermodynamic optimization of an entire crude oil distillation unit - Farhat, Imen; Hajji, Professor Nejib (IJRDO-Journal of Applied Science, 2019)
The energy use of the crude oil refining industries has risen over the years. This work deals with the simulation, thermodynamic analysis and optimization of an entire crude oil distillation unit (CDU) composed of an atmospheric distillation unit (ADU), a vacuum distillation unit (VDU), Train heaters (TH), Stabilizer Unit (SBU) and Splitter Unit (SPU). The obtained results showed that the total exergy losses are about 120 MW for a crude flow rate of 561t.h-1: 69% of those losses are located in the ADU, 21.5 % in the VDU, 7 % in the exchange trains, 2 % in The stabilization column and 0.5% in the splitter column.  The efficiency of the furnace and that of the atmospheric and vacuum column prove that these equipments can play an important role in improving the unit performance. An optimization study of atmospheric and vacuum unit was carried out by adjusting operating parameters to maximize efficiency. Results showed a considerable economic benefit at no additional cost of equipment without trading off the products qualities.